Attitudes vs. Purchase Behaviors as Experienced Dissonance: The Roles of Knowledge and Consumer Orientations in Organic Market - Hidalgo-Baz, María; Martos-Partal, Mercedes; González-Benito, Óscar (Frontiers in Psychology, 2017)
This research focuses on the incongruity between positive attitudinal responses but a lack of purchase behavior in organic markets. According to cognitive dissonance theory, consumer orientations toward the benefits attributed to organic products (environmental protection, health, hedonic) relieve the dissonance that results from this attitude–behavior incongruity. Knowledge also functions as a transmitter, from positive attitudes to purchase behaviors, thereby reducing the incongruity. Using quota sampling in a survey study, this article tests the hypotheses with linear regression models. The results show that orientations and knowledge improve the congruity between attitudes and purchase behaviors toward organic products. Moreover, interaction effects arise between the environmental protection orientation and knowledge and between the hedonic orientation and knowledge. Increasing knowledge mitigates the difference between attitudes and purchase behaviors, especially for consumers with environmental protection or hedonic orientations. These findings have several important implications for research and practice.